TENORM radiation protection patterns for the sustainable health of workers - Primanti, Afthina; Kusnoputranto, Haryoto; Purwana, Rachmadhi; Gozan, Misri (Public Health of Indonesia, 2023)
Background: Coal production in Indonesia continues to increase to meet national energy needs and export demand. Solid waste from the coal combustion process is estimated to increase significantly. One of the hazardous mining wastes is TENORM, but some TENORM is classified as production goods with economic value. The problem in this research is that the volume of waste containing TENORM is quite large, and the disposal, use, and recycling of TENORM has the potential to cause contamination for workers at the steam power plant and the surrounding environment. Objective: The purpose of this research is to obtain a design model for the protection of the environment and workers against TENORM radioactive waste from coal ash through an analysis of the social and economic perceptions of steam power plant workers regarding TENORM radiation and the effectiveness of TENORM radiation protection education to workers. Methods: A mixed method with a quantitative approach was applied. Data were gathered through field observation utilizing a questionnaire instrument that asked workers working at Steam Power Plant Units 1 – 7 a series of written questions. Results: Prior to Counseling, most Suralaya Steam Power Plant workers had shallow social and economic perceptions of TENORM radiation, with 88 percent unaware of its effects. The majority also paid between 100,000 and 500,000 IDR monthly in medical expenses. All respondents agreed that TENORM radiation safety counseling for Suralaya Steam Power Plant workers was utterly compelling, with acceptance of TENORM and WTP estimates following Counseling being the most important aspect. Conclusion: There was a significant relationship between the WTP variable after Counseling and the variables acceptance of TENORM protection (0.730), TENORM knowledge (0.627) before and after Counseling (after Counseling), and acceptance of TENORM protection (0.648), according to the pattern of protection for the SEM model.